(untitled) (Journal of Misan Researches, 2024)
This research delves into the complexities of cross-cultural communication, emphasizing the crucial role of pragmatics, particularly speech acts, in facilitating effective intercultural interactions. In an increasingly globalized world, understanding the nuances of communication across different cultures is essential. The study conducts a comparative analysis of speech acts—such as requests, apologies, compliments, and directives—across American and British cultural contexts, examining how cultural norms, values, and linguistic conventions shape their expression and interpretation. By employing qualitative and quantitative methods, including discourse analysis and surveys, the research aims to uncover the significant impact of pragmatics on cross-cultural communication. It highlights potential misunderstandings and misinterpretations while proposing strategies to enhance intercultural communication competence. The study draws on speeches by Martin Luther King Jr. and Winston Churchill to illustrate different communication styles shaped by cultural contexts, with King’s emotionally charged rhetoric reflecting American values and Churchill’s firm tone embodying British pragmatism. These findings underscore the importance of understanding cultural differences in communication patterns to improve cross-cultural interactions. The research offers valuable insights and recommendations for individuals, organizations, and policymakers seeking to navigate the complexities of global communication effectively, ultimately contributing to greater harmony and understanding in an interconnected world.